2018
DOI: 10.1002/glia.23310
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytes sustain long‐term productive HIV‐1 infection without establishment of reactivable viral latency

Abstract: The "shock and kill" HIV-1 cure strategy proposes eradication of stable cellular reservoirs by clinical treatment with latency-reversing agents (LRAs). Although resting CD4 T cells latently infected with HIV-1 constitute the main reservoir that is targeted by these approaches, their consequences on other reservoirs such as the central nervous system are still unknown and should be taken into consideration. We performed experiments aimed at defining the possible role of astrocytes in HIV-1 persistence in the br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 94 publications
1
38
0
Order By: Relevance
“…Studies into the reactivation of latently infected HIV ϩ astrocytes with LRAs, including HDACi, PKC agonists, and proinflammatory mediators, have been enigmatic. Some have shown failure to reactivate HIV in astrocytes even in cells with prolonged viral gene expression (41,42), while others demonstrated HIV reactivation in various types of astrocytes (38,43). Our data also indicated significant activation in unsorted HIV ϩ astrocyte populations by vorinostat alone and in combination with IL-1␤.…”
Section: Discussionsupporting
confidence: 57%
“…Studies into the reactivation of latently infected HIV ϩ astrocytes with LRAs, including HDACi, PKC agonists, and proinflammatory mediators, have been enigmatic. Some have shown failure to reactivate HIV in astrocytes even in cells with prolonged viral gene expression (41,42), while others demonstrated HIV reactivation in various types of astrocytes (38,43). Our data also indicated significant activation in unsorted HIV ϩ astrocyte populations by vorinostat alone and in combination with IL-1␤.…”
Section: Discussionsupporting
confidence: 57%
“…Astrocytes may represent an HIV cellular reservoir within the CNS because they are abundant and display a high frequency of infection ( 2 , 52 ). The HIV infection outcome on these cells is less clear, although a previous report has shown that they may survive or undergo cell death, dependent on viral replication or innocent bystander effects including mitochondrial dysregulation, respectively ( 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, there is an increasing appreciation for the ability of tissue resident macrophages to self-renew and potentially serve as a long-lived reservoir of replication-competent virus (Gama et al, 2018;Roszer, 2018;Wong et al, 2019). In addition, neuroepithelial progenitor-derived astrocytes also harbor HIV provirus, though the replication competency and potential for reactivation of this virus in vivo is poorly understood (Al-Harti et al, 2018;Barat et al, 2018). HIV can infect multipotent hematopoietic CD34+ progenitor cells; however, in general during stable therapy detection of HIV DNA in this population is rare and no recovery of replication-competent virus has been demonstrated (Carter et al, 2010;Durand et al, 2012;Josefsson et al, 2012;Sebastian et al, 2017;Zaikos et al, 2018).…”
Section: Other Cell Typesmentioning
confidence: 99%